Tourism : a modern synthesis - Page, Stephen; Connell, Joanne (Australia THOMSON, 2006)
"Tourism can be a challenging subject for students because it is both dynamic and susceptible to economic turbulence and shifts in trends. Tourism: A Modern Synthesis is an essential textbook for tourism students seeking a clear and comprehensive introduction to their studies that addresses these challenges. The authors apply a strong business approach to the subject reflecting developments in the teaching and content of university courses and the text covers both key principles and contemporary themes and issues at a global scale. Among the new features and topics included in this fifth edition are: New and fully updated case studies to reflect current trends and emerging markets including Africa and Asia. Up to date content on disruptive technologies such as Airbnb, low cost airlines, the e travel revolution and future developments. Current debates in sustainable tourism including the anti-tourism movement, plastic use and the Sustainable Development Goals. New content on evolving topics such as future employment, human resource management in tourism and generational marketing. Fully updated statistics and data. This is the ideal guide to Tourism for students across all levels, serving as a point of reference throughout a programme of study"--
Keywords: Tourism